Implementation of Maqasid Al-Syariah Contemporary Perspective - Abd Rauf Muhammad Amin (Journal of Social Transformation and Regional Development, 2021)
Al-DharÅ«riyyÄt al-Khamsah is an important issue in the study of maqasid al-syariah. This has continued to undergo discourse enrichment since al-Juwaini and al-Gazali introduced it. In a sense, scholars from the past to the present have always tried to develop how the mechanism of its application into the real world according to the context of their respective times. Enrichment, innovation, and development of the discourse of the implementation of al-DharÅ«riyyÄt al-Khamsah are considered necessary based on the fact that the needs of modern society are very much different from the needs of society in the past when our scholars discussed this issue. The results show that this matter has been debated in many cases at least the scholarly debate on the arrangement and concept of each item from the five matters. This paper will attempt to introduce the interpretations of contemporary scholars to the mechanism of preserving and defending religion, soul, lineage, intellect, and property.